Programa educativo de atención integral en directivos y docentes para la prevención del aborto en estudiantes de la Institución Educativa Mariscal Oscar R. Benavides Iquitos 2023 - Guerrero Castillo, Yojan (2025)
This evaluative research examines the effect of a comprehensive educational program aimed at strengthening the knowledge of principals and teachers on abortion prevention among students at the Mariscal Óscar R. Benavides Educational Institution in Iquitos, during the year 2023. The research adopted a quasi-experimental design with control and experimental groups, made up of 27 participants each, using a field-based, longitudinal, and univariate methodology, and applying pretest and posttest measurements. The results showed significant improvements in the experimental group, with an increase in the good level of general knowledge on abortion prevention, from 11.1% in the pretest to 88.9% in the posttest, while the poor and acceptable levels decreased significantly. These findings corroborate the hypothesis that a comprehensive educational program on prevention can effectively improve preventive knowledge among principals and teachers, consolidating itself as a key tool in reducing the risk of abortions in the school environment. In conclusion, the program proves to be a practical and adaptable strategy in educational settings with limited access to health services, effectively aligning with public health and education policies.